Beyond the American Colonization Society. Issue 3 (4th March 2016) - Seeley, Samantha
Abstract: This article offers a critical review of scholarship on black colonization and emigration beyond the United States between the 1770s and the 1850s. In 1816, a group of elite white men founded the American Colonization Society (ACS), an organization committed to sending free African Americans outside the bounds of the nation. By 1821, the ACS had secured federal funding for the project and purchased land for the new black colony of Liberia in West Africa. Historians have long disagreed about the aims of the ACS beyond its prejudicial presumption that African Americans did not belong within the nation. This founding debate has obscured the much longer and more diffuse history of colonization thought across the American colonies and the new United States. Well before and after 1816, both black and white activists planned alternative black colonies outside the bounds of the United States in West Africa, Florida, Haiti, Canada, Texas, Mexico, and the American West. This essay briefly reviews the major arguments in the scholarship on the ACS before turning to examine work that has looked beyond Liberia to embrace creative approaches to the scattered field of black colonization and emigration across the Anglo‐Atlantic world. This growing body of scholarship demonstrates ever more forcefully that removal and migration were at the center of conceptions of race, citizenship, and freedom in the early United States.